Analysis of Physics Concepts in Adrenaline Games in the Batu Night Spectacular (BNS) Area - Mohammad Bakhit Mufti; Lely Mutakinati; Nadia Dewi Masithoh (Indonesia Approach Education, 2022)
Adrenaline games are often found in amusement parks, because adrenaline games are one of the keys to attracting people's attention. Indonesia has many entertainment venues spread across various regions. One example of an amusement park in Indonesia is Batu Night Spectacular (BNS). BNS is one of the tourist sites in the city of Malang, East Java, to be precise in the city of Batu. This study aims to analyze the concept of physics in adrenaline games at BNS. The games that will be analyzed are Mega Disco, Crazy Bike, Drop N'Twist, and Gravitron. This research is a qualitative descriptive research using literature review and observation methods. Based on the literature review and observations that have been made, it was found that in the Mega Disco game there is a physics concept of oscillatory motion and rotational motion. Rotational motion is shown by repeated movements to the right and left, while rotational motion is shown in the rotation experienced by visitors' seats. In the Crazy Bike game there is a simple pendulum physics concept and circular motion. A simple pendulum is shown in a swinging motion with a connecting arm, while circular motion is shown in a crazy bicycle swinging 360 ⁰ . In the Drop N'Twist game, there are concepts that are free fall and vertical upward motion. The Gravitron game has the main concept of three forces that occur, namely gravity , frictional force , and normal force . Gravity is influenced by gravity on a band, and frictional force opposes the motion of gravity so that visitors don't fall down . normal motion is towards the center to maintain the visitor's position while the gravitron rotates.